A Stable Fixed-dose Combination Tablet of Pseudoephedrine and KOB Extracts for the Extended Release - Hwang, C.-J.; Park, M.-H.; Jung, H.-W.; Park, Y.-K.; Kim, Y.-H.; Kang, J.-S.; Cho, C.-W. (Drug Research, 2013)
Allergic rhinitis (AR) is characterized by inflammation of the nasal mucosa with hypersensitivity resulting from seasonal or perennial responses to specific environmental allergens and by symptoms like nasal rubbing, sneezing, rhinorrhea, lacrimation, nasal congestion and obstruction, and less frequently cough. KOB extracts, which is a polyherbal medicine consisting of 5 different herbs (Atractylodes macrocephala, Astragalus membranaceus, Saposhnikovia divaricata, Ostericum koreanum and Scutellaria baicalensis) had commonly been used for the treatment of various allergic diseases showed an anti-allergic effect by modulating mast cell-mediated allergic responses in allergic rhinitis, recently. On the other hand, pseudoephedrine is a sympathomimetic amine commonly used to relieve congestion in patients with allergic rhinitis and common colds. Considering the KOB’s therapeutic mechanism, the combination with pseudoephedrine would be suitable for allergic rhinitis. This study is to obtain an effective extended release formulation using pseudoephedrine and KOB extracts to reduce side effects of drug due to repeated dosing and improve the compliance of patients for treatment of rhinitis and nasal decongestion. So, the fixed-dose combination tablet of pseudoephedrine and KOB extracts was prepared by direct compression and characterized by drug content, flowing characteristics and dissolution test. The drug content of baicalin of KOB extracts was within the range of 95–105% except for T1 formulation. The hardness and friability values of all formulations ranged from 9 to 13 kp and less than 1%, respectively. Taken together, T4 or T8 could be a stable fixed-dose combination tablet for extended release of pseudoephedrine and KOB extracts for nasal rhinitis.
Keywords: allergic rhinitis; KOB extracts; pseudoephedrine; fixed-dose combination; extended release